Development Of 5.8 GHz Microstrip Parallel Coupled Line Bandpass Filter For Wireless Communication System - Othman, Mohd Azlishah; Sinnappa, Mohan; Husain, Mohd Nor; Abd Aziz, Mohamad Zoinol Abidin; Ismail, Mohd Muzafar (Engg Journals Publications, 2013)

(untitled)
This paper aim to present the design technique, parameter analysis, real prototype fabrication and measurement results compare to simulation of 5.8GHz rectangular microstrip inset feed patch antenna. The antenna design calculation, simulation study and practical measurement results are well presented and compared. This study would be useful to realize low cost 5.8GHz rectangular microstrip patch antenna for any appropriate system developments and investigate the parameter study. The information shared is aimed to serve the similar scientific field and improve the system features.